PENGARUH FINANCIAL DISTRESS, SIZE, LEVERAGE, OPERATING CASH FLOW, AUDIT QUALITY, OWNERSHIP CONCENTRATION, DAN GROWTH DENGAN GFC SEBAGAI VARIABEL MODERATING TERHADAP MANAJEMEN LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2007-2017) - Hetami, Muhammad Nighwan; Wahyudi, Sugeng (Diponegoro Journal of Management, 2021)
The aim of this paper is to analyze the effect of financial pressure, size, leverage, operating cash flow, audit quality, ownership concentration, and growth as independent variables on earnings management as the dependent variable, and the global financial crisis as a moderating variable. This paper uses Discretionary Accruals as a proxy for earnings management which is calculated using a modified Jones model. The data selection method used was purposive sampling. The total sample used was 50 manufacturing companies listed on the IDX in 2007-2017. Data analysis was performed using multiple linear regression analysis method. Our results showed that financial distress, leverage, operating cash flow, ownership concentration had a significant negative effect on earnings management. Therefore, audit quality and growth have a significant positive effect on earnings management, while size has no significant effect on earnings management, and the global financial crisis does not moderate the relationship between financial distress and size on earnings management.